Biotech fast forward - Abd Razak, Dzulkifli (2005)
Budget 2006 has given a boost for biotechnology which is likely to create 280,000 jobs by 2020. THE biotechnology sector has never had it so good this year. The official "seal of approval", so to speak, was given in April, when the Government launched the National Biotechnology Policy at the inauguration of BioMalaysia 2005. Under the policy, strategies and more initiatives to further develop the sector were outlined. It was given another boost last week when the Prime Minister, in his Budget 2006 speech, announced the setting up of the Malaysian Life Sciences Capital Fund. This fund would pool investments from various institutions, including governmentlinked companies. With an initial RM100 million investment by the Government, the fund seeks to spur biotechnology in at least three strategic areas — agriculture, health (including pharmaceuticals and nutraceuticals) and industrial biotechnology.